2003
DOI: 10.1002/adfm.200390009
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Morphology of Nanocrystal–Polymer Composites for Solar Cells

Abstract: We have shown recently that the use of high aspect ratio inorganic nanorods in conjunction with conjugated polymers is a route to obtaining efficient solar cells processed from solution. Here, we demonstrate that the use of binary solvent mixtures in which one of the components is a ligand for the nanocrystals is effective in controlling the dispersion of nanocrystals in a polymer.By varying the concentration of the solvent mixture, phase separation between the nanocrystal and polymer could be tuned from a mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
407
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(419 citation statements)
references
References 28 publications
6
407
1
5
Order By: Relevance
“…Huynh et al found that the use of a binary solvent mixture in which one solvent is a ligand to nanocrystals could help the dispersion of the nanocrystals inside polymer matrix. 138 By using a benzene-1,3-dithiol chemical vapor annealing, Wu et al found that ligand exchange and phase separation occurred, which was responsible for efficiency improvement. 139 Other nanocrystals were also used to fabricate hybrid devices, for example silicon nanocrystals, CdS, ZnO, GaAs, and PbS.…”
Section: Polymer-inorganic Hybrid Solar Cellsmentioning
confidence: 99%
“…Huynh et al found that the use of a binary solvent mixture in which one solvent is a ligand to nanocrystals could help the dispersion of the nanocrystals inside polymer matrix. 138 By using a benzene-1,3-dithiol chemical vapor annealing, Wu et al found that ligand exchange and phase separation occurred, which was responsible for efficiency improvement. 139 Other nanocrystals were also used to fabricate hybrid devices, for example silicon nanocrystals, CdS, ZnO, GaAs, and PbS.…”
Section: Polymer-inorganic Hybrid Solar Cellsmentioning
confidence: 99%
“…5,6,7 of the Ag peak for these two composites was adjusted to correct for a small static charging. The same energy shift was used to correct the C 1s and S 2p spectra ( Figure 2b and 2c, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Such hybrid nanomaterials combine the electronic properties of inorganic materials with the low-temperature solution processability of polymers [1]. Different inorganic nanoparticles such as TiO 2 [2][3][4], ZnO [5][6][7][8], PbS [9,10], CdS, CdSe or CdTe [11][12][13][14], and PbSSe [15] have been used as n-type semiconductor to produce hybrid bulk heterojunction solar cells with efficiencies up to 5.5%.…”
Section: Introductionmentioning
confidence: 99%